Analisis Miskonsepsi IPAS Berbasis Four Tier Diagnostic Test pada Materi Ekosistem di SD Negeri Growong Kidul 02 (Jurnal Arjuna : Publikasi Ilmu Pendidikan, Bahasa dan Matematika, 2025)
Students' success in mastering Natural and Social Sciences competencies is often hampered by misconceptions that go undetected by teachers. Misunderstandings of basic ecosystem concepts risk hindering mastery of more complex material at the next level. This study aims to analyze students' misconceptions on ecosystems using a more accurate diagnostic instrument than conventional tests. This study was conducted at Growong Kidul 02 elementary school using a quantitative descriptive approach. The main instrument used was the Four Tier Diagnostic Test, designed to measure students' answers, their level of confidence in their answers, their reasons, and their level of confidence in their reasons. The results revealed that the use of the four-tier diagnostic test effectively differentiated students' understanding categories between those who understood the concept, those who did not understand it, and those who had misconceptions. Based on the analysis, a significant prevalence of misconceptions was found in the indicators of interactions between ecosystem components and energy flow. These findings prove that the four-tier diagnostic method provides more detailed information about students' cognitive structure than conventional multiple-choice tests. The implications of this research emphasize the importance for educators of implementing regular diagnostic assessments as a foundation for designing appropriate remedial learning strategies. By identifying the root causes of misconceptions, teachers can provide more targeted instructional interventions to optimally improve students' conceptual understanding.